Correlation Between Level of Parental Knowledge About Visual Acuity and The Incidance of Retractive Errors in Children with Disabilities in Mawar Putih Special School - Shinta Amelia Astuti; Fitri Yati; Rumpoko Triatmono; Anidaul Fajriyah (Yayasan Darussalam Bengkulu, 2026)
Refractive error of the eye is a condition where the image is firm. It is not formed on the retina but on the front or back of the yellow spot and is not located at a single sharp point. Knowledge is one of the factors that plays a role in developing a person's health. The aim of this study was to analyze the relationship between the level of parental knowledge about visual acuity and the incidence of eye disorders in children with disabilities. The aim of this study was to analyze the relationship between the level of parental knowledge about visual acuity and the incidence of eye disorders in children with disabilities. This research is a descriptive correlation with a cross-sectional approach where research subjects were obtained using total sampling techniques (n=75). The relationship between parent level of knowledge about visual acuity and the incidence of eye disorders was analyzed using the Spearman Rank test. There were 34 parents (45.3%) who had sufficient knowledge about sharp vision and 31 students (41.3%) who had myopia. The relationship between the two shows a p value = 0.033. Conclusion: There was a relationship between level of parental knowledge about visual acuity and the incidence of refractive errors in children with disabilities in Mawar Putih special school.